Peran Guru dalam Implementasi Amaliah Aswaja Kepada Peserta Didik Pada Mata Pelajaran Ke-NU-an di SMK Ma'arif 1 Kebumen - Luthfi Reisya Freshtiana; Agus Nur Soleh (Tarbi: Jurnal Ilmiah Mahasiswa, 2026)
The Role of Teachers in Implementing Amaliah Aswaja to Grade X Students in the NU Subject at SMK Ma'arif 1 Kebumen.The objectives of this research are: (1) to determine the role of teachers in implementing amaliah aswaja in the NU subject for class X students at SMK Ma'arif 1 Kebumen; (2) to determine the amaliah aswaja of students in the SMK Ma'arif 1 Kebumen environment; (3) to determine the impact of the implementation of amaliah aswaja on the character of students at SMK Ma'arif 1 Kebumen.This research is a qualitative research. The subjects in this study were the Principal, NU-an Teacher, OSIS Advisor Teacher, and Grade X students, namely TEI, DKV, PHTL, TSM. The method used in this study is a descriptive method. Data collected through observation, interviews, and documentation. The data analysis used is data reduction, data presentation, and drawing conclusions.The results of this study show that; (1) The role of teachers in implementing amaliah aswaja for students in the NU subject at SMK Ma'arif 1 Kebumen (2) the form of amaliah aswaja is generally implemented well, where all school parties at SMK Ma'arif 1 Kebumen instill amaliah aswaja through habituation (3) the impact of implementing amaliah aswaja on the character of students has a very positive impact because in the formation of character, students have a sense of religion, discipline, and tolerance towards mass organizations.